Field and computational investigation of elastomeric bearings in high-demand steel girder application. (November 2019) - Han, Liwei; Belivanis, Konstantinos V.; Helwig, Todd A.; Tassoulas, John L.; Engelhardt, Michael D.; Williamson, Eric B.
Abstract: Steel-reinforced elastomeric bearings are commonly used on short- to moderate- span prestressed concrete girder systems. This type of bearing has also been used on a limited number of steel girder applications where the girders have long spans, large reactions, and complex movements, referred to herein as "high demand" bearing applications. Whereas such systems would typically use pot or disc bearings, elastomeric bearings may offer both cost and performance advantages. However, isolated cases were encountered in which some of the elastomeric bearings in such applications had performed poorly. This paper documents the results of a research study including three-dimensional finite-element thermal-structural analysis and field instrumentation measurements of damaged elastomeric bearings on a horizontally curved trapezoidal steel box girder bridge in Austin, Texas to investigate the use of large-sized elastomeric bearings in high demand steel girder applications. The study shows that the bearing damage was not caused by thermal or truck-induced girder movements, but the excessive transverse rotational deformation due to inadequate control of the top the pier seat geometry during construction. The results of this study support the use of large-sized steel-reinforced elastomeric bearings in high-demand steel girder applications such as trapezoidal steel box girder systems. Recommendations on large-sized bearing design and construction are made based on the results of this study.